Increasing Dietary Medium-Chain Fatty Acid Ratio Mitigates High-fat Diet-Induced Non-Alcoholic Steatohepatitis by Regulating Autophagy - Mu-En Wang (Nature Portfolio, 2017)
Abstract Previous studies have demonstrated that saturated fatty acids (SFAs) are more lipotoxic than unsaturated fatty acids (UFAs) in inhibiting hepatic autophagy and promoting non-alcoholic steatohepatitis (NASH). However, there have been few studies have investigated the effects of carbon chain length on SFA-induced autophagy impairment and lipotoxicity. To investigate whether SFAs with shorter carbon chain lengths have differential effects on hepatic autophagy and NASH development, we partially replaced lard with coconut oil to elevate the ratio of medium-chain fatty acids (MCFAs) to long-chain fatty acids (LCFAs) in a mouse high-fat diet (HFD) and fed mice for 16 weeks. In addition, we treated HepG2 cells with different combinations of fatty acids to study the mechanisms of MCFAs-mediated hepatic protections. Our results showed that increasing dietary MCFA/LCFA ratio mitigated HFD-induced Type 2 diabetes and NASH in mice. Importantly, we demonstrated that increased MCFA ratio exerted its protective effects by restoring Rubicon-suppressed autophagy. Our study suggests that the relative amount of LCFAs and MCFAs in the diet, in addition to the amount of SFAs, can significantly contribute to autophagy impairment and hepatic lipotoxicity. Collectively, we propose that increasing dietary MCFAs could be an alternative therapeutic and prevention strategy for Type 2 diabetes and NASH.